Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1364/oe.21.016263
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the role of the lateral photo-Dember effect in the generation of terahertz radiation using a metallic mask on a semiconductor

Abstract: Pulses of coherent terahertz radiation can be efficiently generated by a lateral diffusion current after ultrafast generation of photo-carriers near a metal interface on the surface of a semiconductor, this is known as the lateral photo-Dember effect. We investigate how the emission depends on the pump spot position, size, power and how it is affected by the application of an applied external bias. We study the role of the metallic mask and how it suppresses emission from the carriers diffusing under it due to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
24
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 15 publications
0
24
0
1
Order By: Relevance
“…This is attributed to the device emitting both from photoDember currents and the intrinsic net lateral current due to the Schottky effects. The emission asymmetry with angle is due to the asymmetric nature of LPD emission in general [18] and the asymmetrical geometry of the DM emitter element. A circular Fig.…”
Section: Angular Dependence Of Emission and Radial Polarizationmentioning
confidence: 99%
See 1 more Smart Citation
“…This is attributed to the device emitting both from photoDember currents and the intrinsic net lateral current due to the Schottky effects. The emission asymmetry with angle is due to the asymmetric nature of LPD emission in general [18] and the asymmetrical geometry of the DM emitter element. A circular Fig.…”
Section: Angular Dependence Of Emission and Radial Polarizationmentioning
confidence: 99%
“…This paper explores beam steering using large-area emitters that generate THz radiation via diffusion currents, also known as the lateral photo-Dember (LPD) effect [17][18][19] and Schottky potentials [20,21]. LPD and Schottky potential-based double metallic emitters have been found to have similar spectral bandwidth with photo-conductive emitters [19,20] .…”
mentioning
confidence: 99%
“…However the ionization process also requires high-power amplified ultra-short laser pulses and the generated THz field in both schemes exhibits a conical wavefront. Recently, it was demonstrated that transient photo-currents excited on semiconductor surfaces by short (100 fs) optical pulses can have a large radial component due to the photo-generated charge density gradients20212223 and anisotropic conductivity24. This mechanism can provide efficiency, simplicity and tunability (i.e., dynamic control) in generation of THz beams with a tailored polarization state (e.g., radially-polarized THz beam) since the polarization state is governed by the shape of the optical beam and does not require bias.…”
mentioning
confidence: 99%
“…More recently, photo-currents within the plane of the semiconductor surface were harnessed as a process for THz pulse generation [13][14][15][16][17][18]. Using normal incidence optical excitation, significant emission was observed in systems with an asymmetric photoexcited charge density distribution across the surface formed at the edge of a metallic contact [13,14].…”
mentioning
confidence: 99%
“…13 and 15 suggest that the metal layer is not required if a high gradient is present, whereas Refs. [16][17][18] suggest that the metal layer is crucial for emission. This has raised questions over the distribution of photo-current responsible for the lateral photo-Dember effect.…”
mentioning
confidence: 99%